2015
DOI: 10.1530/eje-15-0464
|View full text |Cite
|
Sign up to set email alerts
|

Cushing's syndrome: update on signs, symptoms and biochemical screening

Abstract: Endogenous pathologic hypercortisolism, or Cushing’s syndrome, is associated with poor quality of life, morbidity and increased mortality. Early diagnosis may mitigate against this natural history of the disorder. The clinical presentation of Cushing’s syndrome varies, in part related to the extent and duration of cortisol excess. When hypercortisolism is severe, its signs and symptoms are unmistakable. However, most of the signs and symptoms of Cushing’s syndrome are common in the general population (e.g. hyp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
161
0
23

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 294 publications
(185 citation statements)
references
References 42 publications
1
161
0
23
Order By: Relevance
“…Further, in our study, owners were not aware of their answers to the previous questionnaires, which could, however, have helped them to assess the improvement of clinical signs between the first and further rechecks. On the other hand, clinical signs might not only be related to the extent but also to the duration of cortisol excess, a phenomenon which has been documented in human medicine (Nieman, 2015). Finally, timing of the ACTH-stimulation test in relation to trilostane administration has an influence on the magnitude of the cortisol concentration and stimulation, which in turn could lead to a lack of correlation between clinical signs and cortisol concentrations.…”
Section: Discussionmentioning
confidence: 99%
“…Further, in our study, owners were not aware of their answers to the previous questionnaires, which could, however, have helped them to assess the improvement of clinical signs between the first and further rechecks. On the other hand, clinical signs might not only be related to the extent but also to the duration of cortisol excess, a phenomenon which has been documented in human medicine (Nieman, 2015). Finally, timing of the ACTH-stimulation test in relation to trilostane administration has an influence on the magnitude of the cortisol concentration and stimulation, which in turn could lead to a lack of correlation between clinical signs and cortisol concentrations.…”
Section: Discussionmentioning
confidence: 99%
“…They often emerge on different parts of athletes' body, on the breasts and abdomen of pregnant women, in teenagers during the peak of their growth, and in over weighted people. [5][6][7][8] Etiologic factors of striae have not been completely revealed. Skin stretch may result in explosive degranulation of mast cells with consequent destruction of elastin and collagen fibers.…”
Section: Introductionmentioning
confidence: 99%
“…9 Cushing syndrome or long term administration of topical/oral corticosteroids may cause the developing of striae. 5,[10][11][12][13] Genetic susceptibility can definitely have a major role as well; however, the precise mechanism has not completely elucidated. Tung et al performed some accurate genome analysis and demonstrated the collapse of elastic microfibrils as the etiology of some cases of striae distensae.…”
Section: Introductionmentioning
confidence: 99%
“…Para estabelecer o diagnóstico da Síndrome de Cushing são necessários ao menos dois de três testes alterados (118) .…”
Section: Corticotropinomasunclassified
“…Em radioimunoensaios convencionais, o valor de dosagem de ACTH utilizado para essa distinção é de 10 ng/L (118)(119)(120) . Confirmado o hipercortisolismo ACTH dependente, a avaliação hipofisária com ressonância magnética de hipófise é realizada.…”
Section: Corticotropinomasunclassified